Description of the final instar larva of Rhionaeschna vigintipunctata (Ris, 1918) (Odonata: Aeshnidae) - Rodríguez, José Sebastián; Molineri, Carlos (Zootaxa, 2014)
The final instar larva of Rhionaeschna vigintipunctata (Ris) (Odonata, Aeshnidae) is described for the first time. The description is based on a series of mature female larvae collected in Tucumán (NW Argentina) and reared to imago. It shares the U-shaped distal excision of epiproct with other larvae of the Marmaraeschna group (only R. pallipes and R. brevicercia known from this stage); but the minute tubercle at each side of the cleft of ligula is absent. Other characters unique to R. vigintipunctata include: open ligula (vs. closed in other "Marmaraeschna"), and mandibular formula. A table to distinguish the larvae of the three species of "Marmaraeschna" and biological and distributional data of R. vigintipunctata are included.